Reading housing satisfaction parameters over housing mobility in the redevelopment process: Sarigol, Istanbul, Turkey - Markoc, Ilkim (Cogent social sciences, 2017)
In urban transformation processes, three different types of housing mobility can be observed. For those mobility types, distinct satisfaction parameters come into question. The scope of this research is, to define these satisfaction parameters for different mobility groups. Sarigol, a housing redevelopment site in Gaziosmanpasa, Istanbul, which mainly consists of Roman inhabitants, was chosen as a case study for this research. The site is very suitable for the case study because of its social, economic and geographical dynamics. Housing mobility decisions, which are seen during the redevelopment process, can be classified as the determinants in terms of grouping the users in the site through in-depth interviews. In the study, user groups were conceptualized as: stabiles, departers and new comers. The intense housing mobility occurred during the redevelopment process brought along a change in the population structure as experienced in the fieldwork. Such that, residents who have similar cultural, social and economic backgrounds left the site and people who have distinctive social values settled in their place. People from various cultural, economic and social backgrounds were forced to live within the same social environment. Moreover, the change created various physical, social and economic problems in the site. Those problems created dissatisfaction for different user groups in different contexts. While the inhabitants were psychologically and economically affected during the redevelopment process; changes in the quality of users’ lives were observed. As a conclusion, different satisfaction codes emerged for those groups who display distinct housing mobility patterns were presented.